The Good Lives Model (GLM): An Evaluation of GLM Operationalization in North American Treatment Programs. (February 2014) - Willis, Gwenda M.; Ward, Tony; Levenson, Jill S.
The good lives model (GLM) has become an increasingly popular theoretical framework underpinning sex offender treatment programs, and preliminary research suggests that the GLM may enhance the efficacy of programs that adhere to the Risk, Need, and Responsivity (RNR) principles. However, this potential rests on the appropriate operationalization of the GLM in practice. Operationalized appropriately, the GLM aims to facilitate risk reduction alongside equipping clients with the tools to live personally meaningful and fulfilling lives. However, misguided operationalization of the GLM could result in ineffective treatment and ultimately higher rates of reoffending. This article presents findings from a multisite study exploring how the GLM has been operationalized and the degree to which the GLM has been integrated in a sample of 13 North American treatment programs. A comprehensive coding protocol was developed that included items related to program aims and client induction/orientation, assessment, intervention planning, intervention content, and intervention delivery. Each site was visited and items were rated through a review of program documentation, interviews with program directors/managers, and observations of treatment groups. Findings from inductive (how the GLM was operationalized) and deductive (the extent to which the GLM was integrated) analyses are presented and GLM consistent and inconsistent practices are highlighted. The article concludes with suggestions for ways in which program responsiveness to the GLM could be enhanced.